Inhibition of Human Liver Carboxylesterase (hCE1) by Organophosphate Ester Flame Retardants and Plasticizers: Implications for Pharmacotherapy. (8th July 2019) - Phillips, Allison L; Stapleton, Heather M
Abstract: Organophosphate ester (OPE) flame retardants and plasticizers, consumer product additives with widespread human exposure, were evaluated for their effect on the activity of purified human liver carboxylesterase (hCE1). Four of the 15 OPEs tested had IC50 values lower than 100 nM, including triphenyl phosphate (TPHP), 2-ethylhexyl diphenyl phosphate (EHDPHP), 4-isopropylphenyl diphenyl phosphate (4IPPDPP), and 4- tert -butylphenyl diphenyl phosphate (4tBPDPP), as did 4 of the commercial flame retardant mixtures tested. Because hCE1 is critical for the activation of imidapril, an angiotensin-converting enzyme-inhibitor prodrug prescribed to treat hypertension, the most potent inhibitors, TPHP and 4tBPDPP, and an environmentally relevant mixture (house dust) were further evaluated for their effect on imidapril bioactivation in vitro . TPHP and 4tBPDPP were potent inhibitors of hCE1-mediated imidapril activation ( K i  = 49.0 and 17.9 nM, respectively). House dust extracts (100 µg/ml) also caused significant reductions (up to 33%) in imidapril activation. Combined, these data suggest that exposure to OPEs may affect pharmacotherapy.